Validitas Media Pembelajaran Kimia Berbasis Augmented Reality (AR) Menggunakan Assemblr Edu pada Materi Hidrokarbon - Fatma Tahir; Astin Lukum; Masrid Pikoli; Lukman A.R. Laliyo; Akram La Kilo; Erga Kurniawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the level of validity of Augmented Reality (AR)-based chemistry learning media using the Assemblr Edu platform on hydrocarbon material. This learning media was developed through the 4D development model (Define, Design, Develop, Disseminate). Validation was carried out by three experts using an instrument in the form of a validation media sheet that includes aspects of content, visual appearance, interactivity, and suitability with learning objectives. The validation results showed that the developed learning media obtained a validity score of 96.39% and was included in the